Approach speed, last step characteristics and take-off accuracy of T36 class paralympic long jumpers - Theodorou, A. S.; García-Fresneda, A.; Torralba Jordan, M. A.; Padullés, J.-M.; Padullés, X.; Kotzamanidou, M. C.; Panoutsakopoulos, V. (ISBS Proceedings Archive (Michigan), 2021)
The purpose of this study was to examine the approach speed (VAPP), the characteristics of the last three steps and the accuracy of foot placement at the take-off board (TTB) in T36 Paralympic long jumpers. Nine male finalists in the T36 Class long jump event who competed at the 2012 London Paralympics were analyzed using high speed video cameras and a speed radar gun. Results revealed that VAPP (8.0 ± 0.4 m/s) peaked at a distance of 6.40 ± 3.25 m from the take-off board. Both parameters were significantly correlated with the effective distance of the jump. TTB was 0.14 ± 0.10 m. There was no indication that the last steps were performed using the adequate step length for the proper execution of the "larger penultimate - shorter last step" technique. The adoption of this technique when approaching the take-off board may improve the effectiveness of the approach and aid in achieving a better take-off.